Why do employees come to work when ill? An investigation into sickness presence in the workplace - Ashby, Katherine; Mahdon, Michelle (London, 2010)
"This leading-edge report emphasises that employers should not ignore the impact of sickness presence – working when ill- as it relates to lower performance, higher sickness absence, higher work-related stress and poorer psychological wellbeing."